[Letter from Tromsø Museums styrelse] - Tromsø Museums Styrelse (Unknown, 1892)
Information that Foslie is allowed to resign from his post immediately after New Year. He will be paid from that date until 1892-03-18 provided he travels to Tromsø during the summer of 1892 to finish his algae investigation.